2016
DOI: 10.1007/s10750-016-2913-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agricultural landscape characteristics on the hydrobiota structure in small water bodies

Abstract: Understanding the influence of environmental factors on the hydrobiota structure of small aquatic ecosystems is essential for effective landscape management. In this study of 165 small water bodies situated in the lowland high-productive agricultural landscape of western Poland we evaluate the effect of catchment, buffer zone, water body and water quality parameters on macrophyte functional groups (nymphaeids, elodeids, pleustophytes, helophytes) and zooplankton diversity. The potential pressure of the catchme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
(48 reference statements)
1
13
0
1
Order By: Relevance
“…Studies of kettle holes within central European postglacial landscapes have until recently, focused predominantly on biological interactions between macrophyte plant species and zooplankton with internal water quality parameters and internal biogeochemical cycling at the local scale (Joniak et al, ; Joniak, Kuczynska‐Kippen, & Gabka, ; Joniak, Nagengast, & Kuczynska‐Kippen, ; Kuczynska‐Kippen & Joniak, ; Patzig et al, ). Though the degree of biological interaction among kettle holes is an important current prominent research topic, a detailed hydrological investigation of central European depressional wetlands is presently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of kettle holes within central European postglacial landscapes have until recently, focused predominantly on biological interactions between macrophyte plant species and zooplankton with internal water quality parameters and internal biogeochemical cycling at the local scale (Joniak et al, ; Joniak, Kuczynska‐Kippen, & Gabka, ; Joniak, Nagengast, & Kuczynska‐Kippen, ; Kuczynska‐Kippen & Joniak, ; Patzig et al, ). Though the degree of biological interaction among kettle holes is an important current prominent research topic, a detailed hydrological investigation of central European depressional wetlands is presently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…are to be considered of secondary importance. A number of studies have unequivocally indicated that they can directly affect zooplankton species richness ( [66,67] and references cited in the introduction; but see also further in this section). In addition, lake age [68,69], connectivity, and, in general, the spatial arrangement of the habitat have been acknowledged to play an important structuring role (e.g., [70]; see also [71] for a marine example).…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of the non-arboreal vegetation cover on species richness is consistent with the results of studies that were focused on macrobenthos in lotic habitats (e.g., [73] and literature cited). This could be ascribed to a positive, indirect effect of lateral trophic enrichment on aquatic primary producers, increasing zooplankton diversity by a phytoplankton-mediated bottom up effect or, alternatively, promoting habitat heterogeneity through an increase in aquatic vegetation [66,74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Water was also sampled for measurements of nutrient concentration (total phosphorus and dissolved inorganic nitrogen, which was the sum of nitrate, nitrite, and ammonium nitrogen) and chlorophyll a concentration. Detailed methods for nutrient determination and chlorophyll a concentration (corrected for pheopigments) were described in the previous paper [31].…”
Section: Methodsmentioning
confidence: 99%